Relationship between High Blood Pressure and Microalbuminuria in Children Aged 6-9 Years in a South African Population - Edna Ngoakoana Matjuda; Constance R. Sewani-Rusike; Samuel Nkeh Chungag Anye; Godwill Azeh Engwa; Benedicta Ngwechi Nkeh-Chungag (MDPI AG, 2020)
Though the association between high blood pressure and microalbuminuria is well established in adults, there is a paucity of information on microalbuminuria in children. This study investigated the relationship between high blood pressure and microalbuminuria in 6-9-year-old children. A cross-sectional study, which included 306 primary school children of age 6-9 years old from urban areas (n = 154) and rural areas (n = 152) of the Eastern Cape Province of South Africa, was conducted. Participants' anthropometric data were determined and systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR) were measured and converted to BP percentiles for age, sex and height. Creatinine and albumin concentrations were assayed in early morning midstream urine and the albumin to creatinine ratio (ACR) was calculated. There was a 42.8% prevalence of elevated blood pressure/high blood pressure (E-BP/H-BP) and a 10.1% prevalence of microalbuminuria. Among the 131 children with E-BP/H-BP, 17 had elevated ACR with a prevalence of 13.95%. SBP and HR increased with increasing range of ACR and, furthermore, SBP was significantly (p < 0.05) higher in children with moderately and severely increased ACR. SBP was associated with ACR and increased SBP predicted microalbuminuria (R2 = 0.42, adj R2 = 0.039, B: 0.120, p = < 0.05). In conclusion, microalbuminuria was present in 6-9-year-old South African children of African Ancestry and a weak association was observed with SBP in children.